2018
DOI: 10.3390/coatings8080269
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Ionic Substitutions in Hydroxyapatite Thin Films: Towards Complete Biomimetism

Abstract: Plasma sprayed coatings composed of stoichiometric hydroxyapatite have been extensively used to improve integration of metallic implants in the host bone, as hydroxyapatite (HA) is normally regarded as similar to the mineralized phase of bone. However, these coatings exhibited several drawbacks that limited their success. On the one hand biological apatite is a carbonated-HA, containing significant amounts of foreign ions, having low crystallinity and a small crystals size. This means that it differs from stoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 82 publications
(210 reference statements)
1
79
0
Order By: Relevance
“…Synthetic hydroxyapatite (HA) represents a well-known biocompatible material used as implantable ceramic due to its great chemical and structural resemblance to the inorganic part of human hard tissues [15,16]. Reports from dedicated literature have demonstrated that biological-derived HA (BHA) has some important advantages over synthetic HA.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic hydroxyapatite (HA) represents a well-known biocompatible material used as implantable ceramic due to its great chemical and structural resemblance to the inorganic part of human hard tissues [15,16]. Reports from dedicated literature have demonstrated that biological-derived HA (BHA) has some important advantages over synthetic HA.…”
Section: Introductionmentioning
confidence: 99%
“…To the difference of wet synthesis methods, plasma-assisted techniques offer important advantages, such as: (i) a much faster process for surface deposition, (ii) industrial scaling, (iii) a stoichiometric transfer of the target composition in the synthesized structures, (iv) a better uniformity in terms of morphology and composition, (v) a lower porosity, and (vi) a decreased tendency of the deposited structures to crack or delaminate [100,101]. In the biomedical domain, for the fabrication of CaP coatings for bone implant applications, the most applied plasma-assisted techniques are radio-frequency magnetron sputtering and PLD [102].…”
Section: Methods Overviewmentioning
confidence: 99%
“…This should be remarked on, as the improvement of PEEK surface roughness and wettability is envisioned to promote adhesion, spreading, proliferation, and differentiation of bone cells [68]. In the field of bioactive coatings, biomimetic coatings resembling the composition of natural bone apatite, which is indeed a calcium-deficient, highly-substituted, and poorly crystalline hydroxyapatite [69], are strongly desired, as they are expected to better promote differentiation implant osseointegration compared to highly-crystalline stoichiometric HA or other CaP phases [70][71][72]. Aiming to fabricate highly biomimetic coatings, bone apatite-like (BAL) thin films were deposited on titanium substrate for the first time by direct ablation of a biogenic source; i.e., a deproteinized bovine bone shaft, by making use of IJD technology [73,74].…”
Section: Bioactive Coatings and Thin Films By Pedmentioning
confidence: 99%